Effect of excision of the Y-base on the interaction of tRNAPhe (yeast) with phenylalanyl-tRNA synthetase (yeast). - Krauss, G (1976)
The interaction between tRNAPhe (yeast), from which the Y-base has been removed by acid treatment, and phenylalanyl-tRNA synthetase (yeast) has been investigated by fluorescence competition titrations and sedimentation velocity runs. The binding parameters are given under various ionic conditions. The tRNAPhe-Y still can occupy the specific binding sites on the enzyme. Compared to unmodified tRNAPhe, the binding constant is lowered by more than one order of magnitude. It can be concluded that the Y-base is not necessary for specific recognition of tRNAPhe by the cognate synthetase, it rather may represent a point of attachment for the synthetase.